Improved Microtechnique for the Leptospiral Microscopic Agglutination Test - Cole, John R. (1973)
A method for improving the original Galton microtechnique for detecting leptospiral antibodies has been developed. Simultaneous titrations were performed on 281 animal and human sera and 17 hyperimmune sera with the microscopic agglutination (MA) test and the improved microtechnique. Reproducibility of the improved microtechnique was determined independently on 65 animal sera by two laboratory sections. The results obtained by comparing positive test data from human and animal sera indicated that agreement between the original MA test and this new method exceeded 94%, whereas the original Galton microtechnique and the original MA test agreed in a maximum of 77% of the tests. This study indicates that the results obtained with the improved microtechnique are much more comparable to results obtained with the original MA test than are those obtained with the original Galton microtechnique.